2017
DOI: 10.1093/schbul/sbx179
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Transcranial Direct Current Stimulation Improves Procedural Learning in Nonclinical Psychosis: A Double-Blind Crossover Study

Abstract: The present double-blind crossover study examines the effects of cerebellar transcranial direct current stimulation (tDCS) in controls and in an analogue population to psychosis: individuals reporting elevated symptoms of nonclinical psychosis (NCP). A total of 18 controls and 24 NCP individuals were randomized into conditions consisting of 25 minutes of anodal (active) or sham cerebellar tDCS. Following this, both groups completed a pursuit rotor task designed to measure procedural learning performance. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…The cerebellum is connected to almost every region of the brain, with the exception of the visual cortex and might represent a potential therapeutic target. For example, transcranial direct current stimulation (tDCS) has been applied in patients with non‐clinical psychosis to improve their skills in procedural learning . Understanding the exact location of the cerebellar alterations in schizophrenia and bipolar disorder is important since the location of the cerebellar stimulation influence the effect of brain stimulation in the cerebellum and distant cortical regions .…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum is connected to almost every region of the brain, with the exception of the visual cortex and might represent a potential therapeutic target. For example, transcranial direct current stimulation (tDCS) has been applied in patients with non‐clinical psychosis to improve their skills in procedural learning . Understanding the exact location of the cerebellar alterations in schizophrenia and bipolar disorder is important since the location of the cerebellar stimulation influence the effect of brain stimulation in the cerebellum and distant cortical regions .…”
Section: Discussionmentioning
confidence: 99%
“…If the CTTC circuit does show vulnerability across the psychosis continuum, it will also be important to build a better understanding of cognitive correlates. As noted, procedural learning has already been implicated [33], but it is important to also consider that the CTCC circuit is implicated in modulating a variety of higher-order cognitive functions including working memory [37,38]. Correlates with sway area and cognitive performance in NCP will help to provide early building blocks for understanding how a common circuit dysfunction may contribute to a wide array of symptoms and characteristics, something that has been well established in formal psychosis with theories such as cognitive dysmetria [24,25], but has not been investigated at the lower end of the psychosis continuum.…”
Section: Introductionmentioning
confidence: 90%
“…Specifically, in a double-blind, crossover paradigm, NCP and control participants completed a motor-learning pursuit rotor task after cerebellar transcranial direct current stimulation at one visit, and after a sham (placebo) stimulation at the other visit. The results indicated that, following the sham condition, NCP participants showed significantly lower rates of motor learning across trials; after the active condition, they performed at comparable rates to controls [33]. However, while this provides some support for a potential continuum of cerebellar vulnerability, currently we lack studies of motor behavior that would serve to enrich this perspective.…”
Section: Introductionmentioning
confidence: 96%
“…Cerebellar direct current stimulation has been widely used for the treatment of several neuropsychiatric diseases, ranging from movement disorders [21][22][23][24][25] to autism and schizophrenia [26,27], but only few evidence has been reached so far regarding pain therapy.…”
Section: Current Pitfalls For the Use Of Nibs In Pain Treatmentmentioning
confidence: 99%